The Interaction and Colocalization of Sam68 with the Splicing-associated Factor YT521-B in Nuclear Dots Is Regulated by the Src Family Kinase p59fyn - Annette M. Hartmann; Oliver Nayler; Franz Werner Schwaiger; Axel Obermeier; Stefan Stamm (1999)
Alternative pre-mRNA splicing patterns can change an extracellular stimulus, but the signaling pathways leading to these changes are still poorly characterized. Here, we describe a tyrosine-phosphorylated nuclear protein, YT521-B, and show that it interacts with the nuclear transcriptosomal component scaffold attachment factor B, and the 68-kDa Src substrate associated during mitosis, Sam68. Northern blot analysis demonstrated ubiquitous expression, but detailed RNA in situ analysis revealed cell type specificity in the brain. YT521-B protein is localized in the nucleoplasm and concentrated in 5-20 large nuclear dots. Deletion analysis demonstrated that the formation of these dots depends on the presence of the amino-terminal glutamic acid-rich domain and the carboxyl-terminal glutamic acid/arginine-rich region. We show that the latter comprises an important protein-protein interaction domain. The Src family kinase p59(fyn)-mediated tyrosine phosphorylation of Sam68 negatively regulates its association with YT521-B, and overexpression of p59(fyn) dissolves nuclear dots containing YT521-B. In vivo splicing assays demonstrated that YT521-B modulates alternative splice site selection in a concentration-dependent manner. Together, our data indicate that YT521-B and Sam68 may be part of a signal transduction pathway that influences splice site selection.